2014
DOI: 10.1039/c4cc05145a
|View full text |Cite
|
Sign up to set email alerts
|

Generation of aminoborane monomers RR′NBH2from amine–boronium cations [RR′NH–BH2L]+: metal catalyst-free formation of polyaminoboranes at ambient temperature

Abstract: Protonation of MeRNH·BH3 (R = Me or H) with HX (X = B(C6F5)4, OTf, or Cl), followed by immediate, spontaneous H2 elimination, yielded the amine-boronium cation salt [MeRNH·BH2(OEt2)][B(C6F5)4] and related polar covalent analogs, MeRNH·BH2X (X = OTf or Cl). These species can be deprotonated to conveniently generate reactive aminoborane monomers MeRN=BH2 which oligomerize or polymerize; in the case of MeNH2·BH3, the two step process gave poly(N-methylaminoborane), [MeNH-BH2]n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 49 publications
7
74
1
3
Order By: Relevance
“…This was supported by the observation that the attempted synthesis of i Pr 2 NH · B(O i Pr) 3 was unsuccessful on the basis of 11 B NMR spectroscopic analysis of a reaction mixture that contained equimolar amounts of i Pr 2 NH and B(O i Pr) 3 in THF at 20 °C. As anticipated, the addition of acid HX (X = Cl, OSO 2 CF 3 ) resulted in the formation of the addition product i Pr 2 NH · BH 2 X 25. On the basis of these results, we postulate that the first step in the mechanism of the rehydrogenation of aminoboranes is the addition of H–OH across the N=B bond (Scheme ).…”
Section: Resultssupporting
confidence: 53%
“…This was supported by the observation that the attempted synthesis of i Pr 2 NH · B(O i Pr) 3 was unsuccessful on the basis of 11 B NMR spectroscopic analysis of a reaction mixture that contained equimolar amounts of i Pr 2 NH and B(O i Pr) 3 in THF at 20 °C. As anticipated, the addition of acid HX (X = Cl, OSO 2 CF 3 ) resulted in the formation of the addition product i Pr 2 NH · BH 2 X 25. On the basis of these results, we postulate that the first step in the mechanism of the rehydrogenation of aminoboranes is the addition of H–OH across the N=B bond (Scheme ).…”
Section: Resultssupporting
confidence: 53%
“…Inspection of the 11 B NMR spectrum after 2 hrs shows compound 1 and a significant proportion of a new signal assigned to the new monomeric amino–borane HBNHC 4 H 8 , 7 [δ 41.1, d, J (BH) 124 Hz]. This chemical shift and coupling pattern is similar to other, transient, amino–boranes, [17, 42, 43] as well as stable HBNMeC 4 H 8 , 8 ( vide infra ). After 24 hrs the signal due to 7 had essentially disappeared, with 6 now observed as a significant product.…”
Section: Resultsmentioning
confidence: 79%
“…Substituted primary aminoboranes such as methylaminoborane, NMeHBH 2 , are postulated to oligomerize in solution to the cyclic trimer and, with further heating, to N , N ′, N ′′-trimethylborazine. 29 Although the detailed mechanisms of these transformations require additional elucidation, formation of branched oligomers has been confined to reactions of the parent amine-borane, AB. In previous computational studies we 13 a and others 30 showed that this selective oligomerization could proceed via B–H–B bridged intermediates followed by intramolecular attack of NH 2 on the three-coordinate boron (Scheme 3).…”
Section: Discussionmentioning
confidence: 99%